Graphene Sandwiched Mesostructured Li‐Ion Battery Electrodes. Issue 35 (6th July 2016) - Liu, Jinyun; Zheng, Qiye; Goodman, Matthew D.; Zhu, Haoyue; Kim, Jinwoo; Krueger, Neil A.; Ning, Hailong; Huang, Xingjiu; Liu, Jinhuai; Terrones, Mauricio; Braun, Paul V.
Abstract : A deterministic graphene‐sandwiched Li‐ion battery electrode consisting of an integrated 3D mesostructure of electrochemically active materials and graphene is presented. As demonstrations, electrodes with active nanomaterials that coat (V2 O5 @graphene@V2 O5 cathode) or are coated by (graphene@Si@graphene anode) graphene are fabricated. These electrodes exhibit high capacities and ultralong cycle lives (the cathode can be cycled over 2000 times with minimal capacity fade).